Neuromotor performance, prematurity and low birth weight. - Alfredo Alexandre Lopes; Go Tani; José António Ribeiro Maia (Universidade Federal de Santa Catarina, 2011)
There seems to be consensus that intrauterine influences during human development have long-term implications. The hypothesis has been raised that alterations in an individual's life cycle provoke lesions, some of them irreversible. The objectives of this study were: (1) to call attention to the problem of distance effects of neuromotor performance, prematurity and low birth weight in children and youngsters; (2) to present relevant aspects of the conceptual framework of fetal programming and its interpretive relevance for deficits in motor performance and coordination. A Pubmed database search was performed using different key words and their possible combinations. Cross-sectional, longitudinal and case-control studies evaluating motor performance and fetal programming were selected. Motor deficit levels ranged from 4% to 51% in the European population and from 4% to 56% in the North American population. A study involving the Australian population reported a motor coordination deficit of 9.5%. There is no absolute agreement regarding the extent, reversibility and significance of motor deficits in view of the wide variability in deficit levels. The mechanisms that will induce problems in the neuromotor development of children, youngsters and adults under adverse conditions of fetal development are unknown and cannot be compensated for by sensorimotor stimulation.